P164 VERY LONG TERM FOLLOW UP OF PRIMARY TRANSCATHETER PATENT FORAMEN OVALE CLOSURE FOR MIGRAINE CURE. (18th May 2022) - Rigatelli, G; Zuin, M; Gianese, F; Adami, A; Aggio, S; Roncon, L
Abstract: Background and Purpose: Results of previous trials about PFO closure as a treatment for migraine are still doubtful and inconclusive. We sought to evaluate the long–term (>10 years) effectiveness of migraine treatment by means of patent foramen ovale (PFO) closure. Method: From 2006 to 2010, 86 patients (68 female, mean age 40.0 ±3.7 years) with disabling, medication–refractory migraine and PFO were enrolled in a prospective study over a 48–month period. Criteria for transcatheter closure were all the following: presence of a permanent right–to–left shunt (RLS) having a shower/curtain pattern, presence of interatrial septal aneurysm and Eustachian valve, 3 to 4 class Migraine Disability Assessment Score (MIDAS), coagulation abnormalities, and medication–refractory migraine with or without aura. Results: Forty patients (46.5%) (34 females, mean age 35.0±6.7 years, mean MIDAS 35.8 ± 4.7) underwent transcatheter closure. After a mean follow–up of 118.2 ±19.1 months (range 96 to 144), 37 patients continued the follow–up and experienced symptomatic improvement: aura was abolished in the totality of patients along with a durable improvement of migraine throughout the extended follow up also in patients without aura. The mean MIDAS significantly decreased in the closure group (p < 0.0001). Patients with complete migraine resolution presented a shorter history of migraine, a more severe thrombophilic profile, more severe RLS and larger left atrial diameter and volume. Conclusions: Primary transcatheter PFO closure in selected high–risk patients having disabling refractory migraine resulted in abolition of aura and in a sustained reduction in migraine in the very long–term period.